2007
DOI: 10.1158/0008-5472.can-06-3063
|View full text |Cite
|
Sign up to set email alerts
|

Human Mucin 1 Oncoprotein Represses Transcription of the p53 Tumor Suppressor Gene

Abstract: The mucin 1 (MUC1) heterodimeric protein is aberrantly overexpressed in human breast cancers and induces transformation. The MUC1 COOH-terminal subunit (MUC1-C) is targeted to the nucleus of transformed cells, where it interacts with p53 and regulates p53-mediated transcription. The present studies show that MUC1 represses activation of the p53 gene and that MUC1-C occupies the PE21 element in the p53 proximal promoter. Previous work has shown that the Kruppel-like factor 4 (KLF4) transcription factor represse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 38 publications
4
73
0
3
Order By: Relevance
“…It was also shown that KLF4 suppresses p53 expression by directly acting on its promoter, thus providing resistance to DNA damage-induced apoptosis (Wei et al, 2007). Depleting KLF4 from breast cancer cells restores p53 levels and causes p53-dependent apoptosis (Rowland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that KLF4 suppresses p53 expression by directly acting on its promoter, thus providing resistance to DNA damage-induced apoptosis (Wei et al, 2007). Depleting KLF4 from breast cancer cells restores p53 levels and causes p53-dependent apoptosis (Rowland et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of partner proteins have been implicated in modulating the selection of p53 targets. The cellular environment and the relative abundance of these partners under different conditions could obviously tip the life-or-death balance of p53 activity (4,(10)(11)(12)(13)(14)(15). Recently, the zinc finger protein Hzf was found to be involved in opposite arms of the p53 response, providing an important insight into the mechanisms that dictate the life and death decisions of p53 (16).…”
Section: Introductionmentioning
confidence: 99%
“…The cytoplasmic domain (Muc1-c) is targeted toward the nucleus, where it interacts with P53 gene and occupies its promoter region. This makes the kruppel-like factor tightly bound with the promoter region, resulting in suppression of gene P53 [18] [19]. When gene P53 becomes inactive, this leads to suppression of P21 (cyclin dependent-kinase inhibitor) which results in prevention of cyclic arrest.…”
Section: Blocking the Pathway Of The Intrinsic Program Of Cell Deathmentioning
confidence: 99%